2021
DOI: 10.3390/met11060879
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Behavior of Al-7Si-0.4Mg Alloy with Er and Zr Additions

Abstract: In recent years, many efforts have been devoted to the development of innovative Al-based casting alloys with improved high temperature strength. Research is often oriented to the investigation of the effects of minor element additions to widely diffused casting alloys. The present study focuses on Al-7Si-0.4Mg (A356) alloy with small additions of Er and Zr. Following previous scientific works on the optimization of heat treatment and on tensile strength, creep tests were carried out at 300 °C under applied st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In combination with erbium (Er), the addition of Zr to the A356 alloy brought improvement to high-temperature properties, specifically regarding creep, in addition to increasing the maximum hardness achieved by the alloy after aging [157,158]. Huang et al observed both Si 2 Zr and (Al,Si) 3 Zr dispersoids in an Al-7Si-0.3Mg alloy with 0.16% Zr, to whom an improved creep performance was attributed [159].…”
Section: Other Transition Elementsmentioning
confidence: 99%
“…In combination with erbium (Er), the addition of Zr to the A356 alloy brought improvement to high-temperature properties, specifically regarding creep, in addition to increasing the maximum hardness achieved by the alloy after aging [157,158]. Huang et al observed both Si 2 Zr and (Al,Si) 3 Zr dispersoids in an Al-7Si-0.3Mg alloy with 0.16% Zr, to whom an improved creep performance was attributed [159].…”
Section: Other Transition Elementsmentioning
confidence: 99%
“…The effects of microstructure or microstructural stability, either directly correlated to the manufacturing process, or induced by heat treatment or by prolonged high temperature exposure simulating service, have also been considered in other contributions: for the two Al-SiMg alloys differently produced and heat treated by Gariboldi et al [5] and Paoletti et al [6], for the friction stir welded Mg alloy WE54 studied by Álvarez-Leal et al [7], for the dynamic recrystallization in martensitic steels changes reviewed by Derazkola et al [8], the Ni-based alloys investigated by Llizzi et al [9] and Engels [10], and finally the Mo-Si alloys investigated by Krauss et al [11].…”
Section: Mmicrostructural Changes Induced By High Temperature Exposurementioning
confidence: 99%
“…In the case of modified Al-7Si-Mg casting alloys investigated by Gariboldi et al [5], the strengthening role played by nanometric-size precipitate or dispersoids and by their thermal stability at 300 • C for the deformation resistance of the material has been discussed. The amount and morphology of the eutectic Si and of coarse intermetallic phases, both of them at the interdendritic region and responsible for the microstructural damage leading to the final fracture, have also been considered by the above authors.…”
Section: Creep and Creep Modelingmentioning
confidence: 99%